Interstitial rotating shield brachytherapy for prostate cancer. Issue 5 (9th April 2014) - Adams, Quentin E.; Xu, Jinghzu; Breitbach, Elizabeth K.; Li, Xing; Enger, Shirin A.; Rockey, William R.; Kim, Yusung; Wu, Xiaodong; Flynn, Ryan T.
Abstract : Purpose: : To present a novel needle, catheter, and radiation source system for interstitial rotating shield brachytherapy (I‐RSBT) of the prostate. I‐RSBT is a promising technique for reducing urethra, rectum, and bladder dose relative to conventional interstitial high‐dose‐rate brachytherapy (HDR‐BT). Methods: : A wire‐mounted 62 GBq 153 Gd source is proposed with an encapsulated diameter of 0.59 mm, active diameter of 0.44 mm, and active length of 10 mm. A concept model I‐RSBT needle/catheter pair was constructed using concentric 50 and 75 μ m thick nickel‐titanium alloy (nitinol) tubes. The needle is 16‐gauge (1.651 mm) in outer diameter and the catheter contains a 535 μ m thick platinum shield. I‐RSBT and conventional HDR‐BT treatment plans for a prostate cancer patient were generated based on Monte Carlo dose calculations. In order to minimize urethral dose, urethral dose gradient volumes within 0–5 mm of the urethra surface were allowed to receive doses less than the prescribed dose of 100%. Results: : The platinum shield reduced the dose rate on the shielded side of the source at 1 cm off‐axis to 6.4% of the dose rate on the unshielded side. For the case considered, for the same minimum dose to the hottest 98% of the clinical target volume ( D 98% ), I‐RSBT reduced urethral D 0.1cc below that of conventional HDR‐BT by 29%, 33%, 38%, and 44% for urethral dose gradient volumes within 0, 1, 3, and 5 mm of the urethra surface, respectively. Percentages are expressed relative to the prescription dose of 100%. For the case considered, for the same urethral dose gradient volumes, rectum D 1cc was reduced by 7%, 6%, 6%, and 6%, respectively, and bladder D 1cc was reduced by 4%, 5%, 5%, and 6%, respectively. Treatment time to deliver 20 Gy with I‐RSBT was 154 min with ten 62 GBq 153 Gd sources. Conclusions: : For the case considered, the proposed 153 Gd‐based I‐RSBT system has the potential to lower the urethral dose relative to HDR‐BT by 29%–44% if the clinician allows a urethral dose gradient volume of 0–5 mm around the urethra to receive a dose below the prescription. A multisource approach is necessary in order to deliver the proposed 153 Gd‐based I‐RSBT technique in reasonable treatment times.